Insight from Atomistic Simulations of Protonation Dynamics at the Nanoscale1. Issue 6 (11th November 2016) - Dreßler, C.; Kabbe, G.; Sebastiani, D.
Abstract: In this paper, we give an overview of the role of molecular dynamics (MD) simulations in the field of proton exchange membranes. We focus on structural and dynamical findings regarding the topology of hydrogen bond networks and proton diffusion. On the one hand, findings about water‐containing polymer electrolyte membrane fuel cell materials, such as Nafion and liquid containing pore materials are discussed. On the other hand, proton conduction in water‐free systems is elucidated. Here, the focus lies on phosphonic acids, which possess a rigid structure, and polymers based on phosphonic acids.